2011
DOI: 10.1038/ejcn.2011.80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential fatty acids in iron deficient and sleep-disturbed attention deficit hyperactivity disorder (ADHD) children

Abstract: IsraelInattention, hyperactivity and impulsivity constitute the core diagnostic criteria for attention deficit hyperactivity disorder (ADHD) children. Patients generally suffer from sleep disturbance and malnutrition that can account for tiredness during the day, poor concentration, poor eating and depressed mood, along with anemia and an n-3 polyunsaturated acid deficiency. The change of ADHD behavior in children (9-12) was studied, following 10 weeks of treatment with a polyunsaturated acid mixture on six va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 13 publications
1
22
0
4
Order By: Relevance
“…Yehuda and collageus 38 , examined hemoglobin levels and showed that sleep-deprived attention deficit hyperactivity disorder (ADHD) patients also suffer also from iron deficiency. However, Yehuda et al 38 , were not clear if iron deficiency was one of the core symptoms of this pediatric group or it was a consequence of poor food intake habits. Another study of the Yehuda 39 , showed that iron deficiency might be associated with sleep disturbances and lower intelligence quality at pediatric population.…”
Section: Methodsmentioning
confidence: 99%
“…Yehuda and collageus 38 , examined hemoglobin levels and showed that sleep-deprived attention deficit hyperactivity disorder (ADHD) patients also suffer also from iron deficiency. However, Yehuda et al 38 , were not clear if iron deficiency was one of the core symptoms of this pediatric group or it was a consequence of poor food intake habits. Another study of the Yehuda 39 , showed that iron deficiency might be associated with sleep disturbances and lower intelligence quality at pediatric population.…”
Section: Methodsmentioning
confidence: 99%
“…The estimated prevalence of ADHD is about approximately 2% in England and 3-5% in the United States. The etiology of ADHD (which is not a unitary condition) is unknown, although both biological and environmental factors play key roles in the presentation of this disorder [7].…”
Section: Attention Deficit Hyperactivity Disorder and Pufasmentioning
confidence: 99%
“…Neuronal iron deposition causes oxidative stress via the Fenton reaction, which might contribute to elevated oxidative stress observed in the AD brain [109]. Iron-induced oxidative stress has been shown to initiate several apoptotic signaling pathways in neurons [110], and damage proteins such as Ca 2+ -ATPase [111][112][113][114], glutamate transporter [115][116][117], apolipoprotein E [118,119], and Na + /K + -ATPase [111,114,120,121], as well as N-methyl-D-aspartate (NMDA) receptor [122][123][124], and lipids such as cholesterol [125][126][127], ceramides [128,129], and unsaturated fatty acids [130][131][132][133], as well as sphingomyelin [134,135]. Oxidative damage to proteins and lipids by iron can cause synaptic dysfunction and neuronal cell death [136].…”
Section: Ironmentioning
confidence: 99%